Characterization of the Fintech Industry for the Peruvian Market - Hidalgo Castilla, Rafael Daniel (2022)
Financial technology companies in Latin America and the world, typically known as Fintech, are growing at a significant rate. However, a detailed analysis on the main influencers on the success or survival of these technologies remains to be discussed. This research determines the variables and social actors that characterize the Fintech ecosystem. For this purpose, a descriptive design was employed under the methodology of structural analysis, making use of tools such as a panel of experts and the MICMAC software (Matrix of Crossed Impacts Multiplication Applied to a Classification). The results suggest that investment, customer management and behavior due to COVID-19 are considered key variables in the current Fintech market. While the SBS (Superintendency of Banking, Insurance and AFP), Peruvian Fintech companies and clients are considered as the preponderant social actors. The findings constitute a basis for the design and strategic planning of future scenarios aimed at minimizing risks and making the most of the opportunities offered by this industry 4.0 new market.